EFFICACY OF FENBENDAZOLE AND PRAZIQUANTEL-EMODEPSIDE AGAINST INFECTION OF OXYURID EGGS IN GREEN IGUANA (Iguana iguana) - Shelly Kusumarini R; Agnes Tageomi Nakita; Azmi Tsabitah; Reza Yesica (Faculty of Veterinary Medicine Universitas Brawijaya, 2025)
The green iguana (Iguana iguana) is among the most commonly kept pet lizards, yet helminth infections remain a frequent health concern in captivity, often exacerbated by stress, inadequate husbandry, and immunosuppression. Untreated infections compromise animal welfare and contribute to physiological stress. Regular anthelmintic treatment is essential for reducing the parasitic burden and improving reptile health. This study aimed to evaluate the effect of the anthelmintic therapy, fenbendazole and praziquantel + emodepside combination, on the degree of Oxyurid infection in Iguana iguana. Treatment efficacy was assessed based on the interpretation of FECRT outcomes in both the treated and control groups. The 27 infected Iguana iguana were randomly separated into three equal groups. Nine infected iguanas received one of the following treatments: placebo (P0 Control) and fenbendazole at a dose of 25 mg/kg body weight (BW) orally for three days (P1). Praziquantel + emodepside anthelmintic will be administered topically (spot-on) at a dose of 1.12 ml/kg body weight (BW) (P2). The efficacy of the therapies was evaluated on the 30th day after treatment. A fecal examination was carried out utilizing the flotation and McMaster methods. The average FECRT findings revealed that fenbendazole was 100% effective at 25 mg/kg body weight (BW). Subsequently, praziquantel + emodepside combined at 1.12ml/kg body weight (BW) was 90% effective in Iguana iguana infected with Oxyurid. This study found that fenbendazole was more effective dewormer than praziquantel + emodepside in green iguana against Oxyurid.